Endogenous Cushings syndrome is associated with impaired myocardial work efficiency. (4th February 2022) - Sahiti, F; Morbach, C; Ehrlich, K; Detomas, M; Kroiss, M; Lengenfelder, B; Gelbrich, G; Frantz, S; Fassnacht, M; Heuschmann, PU; Hahner, S; Stoerk, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Ministry of Research and Education within the Comprehensive Heart Failure Center, Würzburg OnBehalf: STAAB Cohort Study and CV-CORT-EX Study Background: Endogenous Cushing's syndrome (CS) is associated with increased cardiovascular morbidity and mortality. Long-term remission (LTR) after successful treatment is considered to positively affect the cardiovascular system including the heart. Left ventricular (LV) myocardial work (MyW) based on pressure-strain loops is a novel tool to non-invasively assess LV performance and is considered less load-dependent than LV ejection fraction (LVEF) and global longitudinal strain (GLS). We analyzed LV function in patients with overt CS and CS in LTR in comparison to healthy individuals derived from a local population-based cohort. Methods/Results: In a cross-sectional analysis, we compared n = 31 comprehensively characterized patients with overt CS (mean age 48 ± 12 years, 71% women) and 49 patients with CS in LTR (53 ± 12 years, 77% women) with a control group who underwent transthoracic echocardiography. As control group, we analyzed a population-based sample of apparently healthy individuals (in sinus rhythm, free from CV risk factors, and no significant valve disease) from a population-based cohort: n = 439, 49 ± 11 years, 56% women. MyW assessment was performed off-line using EchoPAC (GE, version 202). Systolic and diastolic blood pressure, HbA1c, and body mass index were significantly higher in patients with either overt CS or CS in LTR when compared to healthy participants (without significant differences between both patient groups). LVEF was equal between all three groups, but GLS was significantly lower in healthy participants and tended to be lower in LTR when compared to patients with CS. Global work index was equal between all three groups, but global wasted work was significantly higher in CS patients when compared to healthy participants, resulting in lower global work efficiency (Table). Conclusion: In contrast to LVEF as established parameter of cardiac function, myocardial work analysis revealed functional alterations in patients with current and previous cortisol excess when compared to healthy individuals derived from a population-based sample. CS patients´ hearts appear to perform larger amounts of wasted work even during long-term remission.